Non wood forest product outlook study for Asia and the Pacific: towards 2010 - Mittelman, A.J.; Lai,C.K.; Byron, R.N.; Michon, G.; Katz E. (Food and Agriculture Organization of the United Nations, 1997)
The 'major importance of minor forest products' has been increasingly recognised as information about the utilisation, trade and management of NWFPs has grown. This study provides an overview of the significance of NWFPs in the Asia-Pacific region, current and likely future trends of product availability and management, the importance of NWFPs to people and economy, and efforts to achieve sustainable forest management in the region. Data regarding NWFPs are scarce, often conflicting and unreliable, even for major commercial species such as rattan, bamboo and tree resin. Yet NWFPs provide important livelihood products and employment for perhaps hundreds of millions of people in the region. Many of these products are traded commercially, but the residents of forest areas are most dependent upon NWFPs for subsistence uses such as food, spices, edible oils, medicines, fodder, forage, stall bedding, green manure, construction material, household utensils, fibre, ornamentation and rituals. Biological 'prospecting' and increasing use of natural medicines and cosmetics are likely to expand international trade in these products. The value of sustainable NWFP harvest could exceed that derived from harvesting timber. There is also a growing demand for endangered plants and animals purchased as trophies and medicines by the region's growing number of affluent consumers. Adverse ecological impacts on forests from overharvesting target species could disturb species interrelationships that are vital for maintaining ecosystem integrity and stability. Much of our knowledge about sustainable NWFP management comes from indigenous technical knowledge, the result of centuries of experimentation by traditional and indigenous peoples. Until recently, this was largely overlooked. Rapid social, cultural and economic changes associated with modernisation have a profound effect on traditional forest people. The overall trend is toward depletion of NWFP resources. Fair trade organisations may become important mechanisms in the future to ensure that collectors and processors receive a fair price for products that are sustainably managed and harvested.